The features of copper oxidation by the data of photocurrent and photopotential studies - Vvedenskii, A.; Grushevskaya, S.; Ganzha, S.; Maksimova, S. (Surface and interface analysis, 2010)
The anodic formation of Cu(I) and Cu(II) oxides on polycrystalline copper in deaerated alkaline solution was investigated using the synchronous transients of current and photocurrent (in the potentiostatic polarization mode) as well as the synchronous transients of photopotential and corrosion potential (in the current interruption mode). It was established that copper is subject to corrosion oxidation by the traces of the dissolved oxygen. The formation of the anodic Cu(I) oxide layer hampers further oxidation of copper. A p‐type conductivity was established for Cu2O and CuO oxides formed on copper during both the anodic polarization and the corrosion. Cu(I) oxide film is thin, i.e. its thickness does not exceed the thickness of the space charge region. The band gap of Cu(I) oxide is equal to 2.2 eV for indirect optical transitions. The anodic polarization in the potential range of CuO formation results in the formation of a thicker oxide film which is a mixture of Cu(I) and Cu(II) oxides. Copyright © 2010 John Wiley & Sons, Ltd.